Analysis Translation Methods of Text Translation in the Novel Al-Liṣ wa al-Kilāb by Najib Mahfuz
Based on Peter Newmark’s translation methodology theory, this study aims to identify and classify the accuracy of the use of diction in the novel Al-Lis